1971
DOI: 10.1073/pnas.68.10.2527
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Host Range Restriction in Escherichia coli Treated with Toluene

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 23 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Thus, phage infection evidently does not abolish restriction in this strain. (ii) As shown by Fleischman and Richardson (7), activity of the restriction system can be observed in toluenized cells of E. coli K strains. The substitution of 5-hydroxymethyl dCTP for dCTP in this system abolishes observed DNA synthesis, presumably because the restriction activity degrades hydroxymethyl cytosine-containing DNA as fast as it is synthesized.…”
Section: Minutes After Nfectionmentioning
confidence: 76%
“…Thus, phage infection evidently does not abolish restriction in this strain. (ii) As shown by Fleischman and Richardson (7), activity of the restriction system can be observed in toluenized cells of E. coli K strains. The substitution of 5-hydroxymethyl dCTP for dCTP in this system abolishes observed DNA synthesis, presumably because the restriction activity degrades hydroxymethyl cytosine-containing DNA as fast as it is synthesized.…”
Section: Minutes After Nfectionmentioning
confidence: 76%
“…A few years later, Charles Thomas joined the department and brought with him a breath of fresh air. Later, in 1971, Roger Fleischman, an MD-PhD student, showed that E. coli cells made permeable with toluene could incorporate hydroxymethylcytosine into their DNA, an event that halted DNA synthesis in strains that restricted phage with nonglycosylated DNA (22). Roger and Judy Campbell, also a graduate student, reproduced this phenomenon in vitro, but the activity proved elusive (23).…”
Section: Glycosylated Bacteriophage T4 Dnamentioning
confidence: 99%
“…A few years later, Charles Thomas joined the department and brought with him a breath of fresh air. Later, in 1971, Roger Fleischman, an MD-PhD student, showed that E. coli cells made permeable with toluene could incorporate hydroxymethylcytosine into their DNA, an event that halted DNA synthesis in strains that restricted phage with nonglycosylated DNA (22). Roger and Judy Campbell, also a graduate student, reproduced this phenomenon in vitro, but the activity proved elusive (23).…”
Section: Glycosylated Bacteriophage T4 Dnamentioning
confidence: 99%